Legal Protection Of Investors In Mutual Fund Investment: Contract Models and Legal Resolution - Sulaiman; Dwi Handini , Fijra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of digital technology and economic growth has encouraged the increasinginterest of Indonesian people in investment, especially through online-based mutual funds.Mutual funds are attractive investment instruments because they are managed by professionalinvestment managers, offer portfolio diversification, and have high accessibility. Nevertheless,this investment still carries risks, both from market fluctuations and potential abuse of authorityby the manager, such as manipulation of financial statements. Therefore, legal protection forinvestors is an important aspect to create certainty and security in investing. This research aimsto analyze the forms of legal protection available to mutual fund investors based on Indonesianlaws and regulations, as well as identify legal remedies that can be taken in the event of lossesdue to negligence or fraud by investment managers. Through normative studies, it is found thatalthough there are regulations governing investor protection, such as Law Number 8 of 1995concerning Capital Markets, there is still a need to strengthen supervision and assertiveness insanctioning to increase the effectiveness of such protection. This study emphasizes theimportance of strengthening regulations and public education to encourage the growth ofhealthy, fair, and sustainable mutual fund investment in Indonesia.